PERANCANGAN MEDIA PEMBELAJARAN FISIKA SMA KELAS XII MATERI KONSEP DAN FENOMENA KUANTUM MENGGUNAKAN ADOBE FLASH CS 6 - Andeni, Khania; Nasir, Muhammad; Zulirfan, Zulirfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Physics for high school consists of abstract subjects generally. Student still think that these abstract subjects have been being a barrier for them in studying physics. Teacher need to be more creative to deliver these abstract physics subjects into concrete subjects. The aims for this research are to develop physics media learning on concept and phenomenon of quantum using Adobe Flash CS 6 and to validate the media become a valid one. The method that has been used in this research is Research and Development (R&D) ADDIE type. The development of media learning including the searching of some problem and potentional background, literature study, product design, design validity and final product. The instrument of this research was quesioner that evaluate media learning which consist of four aspects there are development, pedagogik, content, and technic. Validation mean score for development aspect is 4,22, pedagogik aspect is 4,31, content aspect is 4,30 and technic aspect is 4,30. The result of media validation mean score is 4,28 with very high category and r value = 0,856 with validation category is very high validity. Media learning concept and phenomenon of quantum using Adobe Flash has been successfully developed and has the final result as a valid media. The media can be used at senior high school as an alternative media learningKeyword: Media Learning, Concept and Phenomenon of Quantum, Adobe Flash CS 6.